DWIPURWA DAN POTENSINYA DALAM BAHASA INDONESIA (Dwipurwa and Its Potentiality in Indonesian Language) - Umi Kulsum (SAWERIGADING, 2015)
Dwipurwa (initial syllable reduplication with the vowel replaced by the schwa, partial reduplication) in bahasa Indonesian is unproductive reduplication, unlike dwilingga (full reduplication) which almost can be set up as many words any way. Indonesian people recognize some sorts dwipurwa besides its form in dwilingga. Example the word lelaki, in addition to laki-laki. The use of those two words (both dwipurwa and dwilingga) are interesting to be explored; whether on its same or different meaning. If there is a similarity, there are also things that distinguish the two. In addition, dwipurwa has a tendency of being used in a variety of literature (poetry or song) and also in the social media because it is very dependent on the number of written characters. For instance, dwipurwa that appears in social media is gegara which refers to gara-gara. During these times, there is a tendency to uncover the meaning and new concepts by using dwipurwa, for example, the chosen tetikus (instead of mouse) and jejaring instead of social network. The method used in this research is descriptive while the method of assessment is an equivalent referential method. It is focused on reduplicatedable words that can be both dwipurwa or dwilinggawhich is discussed as a comparison for determining the meaning of dwipurwa itself. The conclusion found in this research is dwipurwa and dwilingga based on the same basic word can have the same meaning, may have the similarity or difference, or totally very different. Dwipurwa has the potentiality to be developed to enrich the terms of certain fields as well as general vocabulary, as recently revealed in a lot of social media.